Trigger algorithms for Alignment and Calibration at the CMS experiment - Tomei, Thiago R.F.P. [UNESP] (My University, 2016)
The data needs of the Alignment and Calibration group at the CMS experiment are reasonably different from those of the physics studies groups. Data are taken at CMS through the online event selection system, which is implemented in two steps. The Level-1 Trigger is implemented on custom-made electronics and dedicated to analyse the detector information at a coarse-grained scale, while the High Level Trigger (HLT) is implemented as a series of software algorithms, running in a computing farm, that have access to the full detector information. In this paper we describe the set of trigger algorithms that is deployed to address the needs of the Alignment and Calibration group, how it fits in the general infrastructure of the HLT, and how it feeds the Prompt Calibration Loop (PCL), allowing for a fast turnaround for the alignment and calibration constants.